Caratteristiche distintive e performance delle piccole imprese italiane orientate all’entrepreneurial marketing - Ferrero, Giancarlo; Buratti, Andrea (Piccola Impresa / Small Business, 2016)
Environmental changes which have been taking place in the last 15 years are leading small business to rethink how they face the new market challenges. Many scholars affirm that Entrepreneurial Marketing Orientation (EMO) could be considered as a valuable answer to the crisis given that it matches innovation (EO) and market understanding (MO). Many scholars have conceptualized EMO but few empirical researches have paid attention to structural characteristics and relative market performances featuring these respect to other firms. Therefore, the paper analyzes the firms’ characteristics distinguishing firms steered to EMO through a questionnaire submitted 545 Italian small businesses. The results show existence of some structural variables of the firms oriented to EMO which have significant differences respect to other firms’ orientation. Moreover, these firms have significant difference even in market performances.